2018
DOI: 10.1159/000489472
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multiple Sclerosis in Iceland

Abstract: Background: In this study, we examined multiple sclerosis (MS) point prevalence in the well-defined island population of Iceland. Methods: This study included all registered residents of Iceland with MS on the prevalence day, December 31, 2007. All included patients met at least one of the following criteria: McDonald criteria; Poser criteria for clinically definite MS, laboratory-supported definite MS, clinically probable MS; or criteria for primary progressive MS. The patients’ medical records were reviewed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 24 publications
4
12
0
3
Order By: Relevance
“…These results point at regional high MS risk in the western coast of Finland. The rates in a large region in Western Finland as shown here in 2010 corroborate the concurrent rates in other Scandinavian countries, such as the nationwide prevalence 188.9/10 5 reported in 2008 in Sweden, crude nationwide prevalence 208/10 5 in 2013 in Norway, 154.5 /10 5 in 2005 in Denmark, and 167.1/10 5 in 2007 in Iceland . Although no exact nationwide prevalence estimation exists in Finland, results here and in a recent report based on a national register information point at a globally high nationwide prevalence of 180‐200/10 5 …”
Section: Discussionsupporting
confidence: 85%
“…These results point at regional high MS risk in the western coast of Finland. The rates in a large region in Western Finland as shown here in 2010 corroborate the concurrent rates in other Scandinavian countries, such as the nationwide prevalence 188.9/10 5 reported in 2008 in Sweden, crude nationwide prevalence 208/10 5 in 2013 in Norway, 154.5 /10 5 in 2005 in Denmark, and 167.1/10 5 in 2007 in Iceland . Although no exact nationwide prevalence estimation exists in Finland, results here and in a recent report based on a national register information point at a globally high nationwide prevalence of 180‐200/10 5 …”
Section: Discussionsupporting
confidence: 85%
“…An east‐west (longitudinal) gradient describing the prevalence of MS has also been reported in some studies, but the results have been inconsistent . A slightly lower prevalence of 167/100 000 in 2007 has been recently reported for Iceland …”
Section: Introductionmentioning
confidence: 78%
“…The rate was clearly higher than the reported nationwide prevalence rates in Sweden and Norway, but lacking standardized Swedish and Norwegian figures, comparisons will be incomplete. The study from Iceland reported a crude and standardized prevalence of 167/100 000, although they had used the US 2000 population for standardization weighing the younger age‐groups slightly more than ESP 2013. Nevertheless, the prevalence in Iceland seems to be on the same level as in NK, representing the lower end of the Nordic prevalence range.…”
Section: Discussionmentioning
confidence: 99%
“…1 Tíðnin er há á Íslandi; algengið var 167/100.000 í desember 2007. 2 Klínísk einkenni endurspegla líffaerafraeðilega staðsetningu bólgubletta í miðtaugakerfinu en ekki valda þó allir bólgublett ir einkennum. Sjúkdómurinn kemur oftast fram í köstum tauga kerfiseinkenna.…”
Section: Inngangurunclassified
“…Rannsóknir hafa líka sýnt að tíðni MS á Íslandi fer vaxandi og þá ekki síst meðal kvenna. 2,16 Kastatíðni laekkaði á meðgöngu miðað við árið fyrir þungun og var laekkunin mest á fyrsta þriðjungi. Þetta er önnur niðurstaða en rannsóknir hafa sýnt, en þá er kastatíðnin yfirleitt laegst á síðasta þriðjungi meðgöngu en þar reyndist munurinn ekki marktaekur í okkar rannsókn.…”
Section: úTkoma Meðgöngu Og Faeðingarunclassified